2016
DOI: 10.5152/tud.2016.90235
|View full text |Cite
|
Sign up to set email alerts
|

The level of knowledge and awareness about prostate cancer in the Turkish male and the relevant effective factors

Abstract: Objective: Our aim was to determine the general knowledge and awareness levels, information sources, and the state of medical check-up for prostate cancer (PCa) and relevant effective factors. Material and methods:The participants were asked to answer to 14 questions of a questionnaire about age, education, economic and social condition, knowledge about PCa, state of being examined and their related factors. According to demographic characteristics of the participants, levels of awareness about PCa, sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…As noted in our study and previous ones, sociodemographics and educational levels have been found to positively impact awareness and overall knowledge of PCa. [ 15 22 28 ] Surprisingly, only 15.9% of our participants who have a positive family history of PCa had good knowledge. This lack of knowledge of PCa necessitates putting efforts into educating men for decision-making regarding PCa screening activities.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As noted in our study and previous ones, sociodemographics and educational levels have been found to positively impact awareness and overall knowledge of PCa. [ 15 22 28 ] Surprisingly, only 15.9% of our participants who have a positive family history of PCa had good knowledge. This lack of knowledge of PCa necessitates putting efforts into educating men for decision-making regarding PCa screening activities.…”
Section: Discussionmentioning
confidence: 79%
“…[ 14 ] Moreover, a study done in Turkey showed that 88.4% of the participant know that PCa is a treatable disease if diagnosed early. [ 15 ] Another study in 2017 in Italy showed that 82.1% of participants informed them that they heard about PCa previously, and 31.8% of them have heard about PCa from a doctor. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, our findings differ from those in Kenya and South Africa, in which ever- screened rates of 5 % and 3.3 %, respectively, have been reported [ 29 , 41 ]. In addition, Turkan et al [ 45 ] in Turkey noted that only 60.8 % of their study participants did not have a medical checkup for Pca in the past 2 years. The observed differences could be due to multiple factors, including difference in screening modality; the South African study focused on the use of PSA, whereas in the index study, we focused on both PSA and DRE.…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings have been reported by other studies conducted in Africa and elsewhere [ 32 , 42 , 43 ]. Contrarily, Turkan et al [ 45 ] in Turkey noted that majority of men did not undergo screening due to negligence (44 %), with only 18.4 % mentioning not knowing about the need for screening, and no one reporting financial difficulties as a barrier. All these factors may contribute to the low screening rate seen in Tanzanian men.…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that the incidence rate is 6.1 per 100,000 and the mortality rate is of 3.8 per 100,000 among Turkish men [1]. Digital rectal examination (DRE) and the biochemical Prostate Specific Antigen (PSA) test are used to screen for prostate cancer [3]. Unlike other types of cancer, most prostate cancers progress slowly; thus, the likelihood of treatment increases when diagnosed early.…”
Section: Introductionmentioning
confidence: 99%